PENGEMBANGAN MEDIA PAPAN INTERAKSI MANUSIA PADA PEMBELAJARAN TEMATIK DI SEKOLAH DASAR - Risa Yuliana; Heri Maria Zulfiati (Universitas Sarjanawiyata Tamansiswa, 2019)
This research aims to develop a â€œhuman interaction boardâ€ teaching media for thematic teaching in the fifth grade of State Elementary School 3 Madusari, Prambanan, Sleman. This is a research and development study which uses Borg and Gallâ€™s development procedures. A development which uses these procedures involves 9 stages, namely research and data collection, planning, initial product development, initial field try out, product revision, operational field try out, and final product revision. The population of this research are all fifth grade students of State Elementary School 3 Madusari, Prambanan, Sleman, there were 22 students. The research samples include all the population. The data collection was conducted by means of questionnaires, observations, and interviews with the class teacher and five students to determine the situation during the teaching process. The data analysis used a descriptive quantitative technique. The research results show that the human interaction board teaching media developed based on Borg and Gallâ€™s development procedures was feasible to be used. This is based on the score percentage achieved from the validator and the students. Material validation results percentage from the lecturer showed a score of 80% with a criterion of feasible to be used. Material validation result percentage from the class teacher showed a score of 83.33% with a criterion of feasible to be used. Media validation results percentage from the lecturer showed a score of 77.33% with a criterion of feasible to be used. Media validation result percentage from the class teacher showed a score of 82.66% with a criterion of feasible to be used. Students scoring percentage achieved during a limited test showed 93% with a criterion of feasible to be used. During a field try out showed 94% with a criterion of feasible to be used. Operational field try out showed 94% with a criterion of feasible to be used.